Effects of soy lecithin concentration on the physicochemical properties of whey protein isolate, casein‐stabilised simulated infant formula emulsion and their corresponding microcapsules. (30th March 2022) - Wu, Feiyang; Chen, Fang; Pu, Yizhen; Qian, Fang; Leng, Youbin; Mu, Guangqing; Zhu, Xuemei
Abstract : The effects of soy lecithin (SL) concentration on the physicochemical properties of whey protein isolate, casein‐stabilised simulated infant formula emulsion (SIFE) and the corresponding microcapsules obtained by spray‐drying were investigated. Soy lecithin addition significantly reduced the apparent viscosity of SIFE. Among the emulsions investigated in this work, the sample prepared with 5% SL demonstrated the smallest average particle size, largest intermolecular repulsion, lowest creaming index and strongest antioxidant capacity. The microcapsule preparations exhibited good re‐dispersibility in water. Spectral shifts in the bands of amides I and II indicated that SL addition can effectively enhance the inter‐ or intramolecular forces of the microcapsules. The high microencapsulation efficiency of 94.03% of the sample prepared with 5% SL could be attributed to favourable interactions between the emulsifier and protein at the adsorption layer. These findings will aid in the development of microcapsules with desirable features from protein–SL mixed systems. Abstract : Effects of soy lecithin concentration on the physicochemical properties in a model of infant formula.